2014
DOI: 10.1182/blood-2013-08-523936
|View full text |Cite
|
Sign up to set email alerts
|

Differential contribution of FXa and thrombin to vascular inflammation in a mouse model of sickle cell disease

Abstract: Key Points Inhibition of FXa or thrombin might be considered to reduce thrombotic complications and vascular inflammation in sickle cell patients. PAR-2 could be a potential target to inhibit vascular pathology associated with sickle cell disease.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

12
96
0
2

Year Published

2015
2015
2023
2023

Publication Types

Select...
6
1
1

Relationship

1
7

Authors

Journals

citations
Cited by 102 publications
(110 citation statements)
references
References 52 publications
12
96
0
2
Order By: Relevance
“…Therefore, we investigated whether increasing the hemopexin levels in the circulation could attenuate coagulation in a mouse model of sickle cell disease. Consistent with our previous study, 25 plasma TAT levels were significantly elevated in sickle cell mice compared to non-sickle controls ( Figure 6). Administration of hemopexin into sickle mice resulted in a 30% decrease of plasma TAT levels; however, this change was not statistically different from TAT levels in vehicle-treated sickle mice ( Figure 6).…”
Section: Effect Of Hemopexin Treatment On Plasma Tat Levels In Sicklesupporting
confidence: 81%
See 1 more Smart Citation
“…Therefore, we investigated whether increasing the hemopexin levels in the circulation could attenuate coagulation in a mouse model of sickle cell disease. Consistent with our previous study, 25 plasma TAT levels were significantly elevated in sickle cell mice compared to non-sickle controls ( Figure 6). Administration of hemopexin into sickle mice resulted in a 30% decrease of plasma TAT levels; however, this change was not statistically different from TAT levels in vehicle-treated sickle mice ( Figure 6).…”
Section: Effect Of Hemopexin Treatment On Plasma Tat Levels In Sicklesupporting
confidence: 81%
“…25 Human hemopexin (Athens Research Technology, Athens, GA, USA) (500 mg in 100 mL PBS per 25 gram of body weight; 280 mmol/kg) was administered to 5-month old male mice via tail vein injection twice a week for two weeks.…”
Section: Administration Of Antibodiesmentioning
confidence: 99%
“…Recently, we showed that PAR-2 but not PAR-1 deficiency on nonhematopoietic cells was also associated with lower IL-6 expression in sickle mice. 2 Together, these data are consistent with in vitro studies describing PAR-2 activation by the TF/factor (F) VIIa/FXa complex, 13 and support the concept that in sickle cell mice this signaling complex induces cellular activation independently of thrombin generation. 2,3,14 Future studies should determine the role of TF pathway inhibitor and endothelial protein C receptor in the regulation of TF/FVIIa/FXa complex signaling in sickle mice.…”
supporting
confidence: 77%
“…Although vaso-occlusive crises and hemolytic anemia are the primary pathologies, SCD is also associated with chronic vascular inflammation and activation of coagulation. [1][2][3] This hypercoagulable state is characterized by increased tissue factor (TF) expression and elevated levels of thrombin generation measured by thrombin-antithrombin (TAT) complexes. 4 We have recently shown that short-term inhibition of all sources of TF in sickle mice attenuates activation of coagulation and reduces endothelial cell (EC) activation and systemic inflammation measured by plasma levels of soluble vascular cell adhesion molecule 1 (sVCAM-1) and interleukin-6 (IL-6), respectively.…”
mentioning
confidence: 99%
“…Также можно отметить антиапоптозный эф-фект активированного протеина С, который также влияет на трофику эндотелия сосудов [6]. Новые пероральные антикоагулянты -ингибитор тромби-на дабигатран и ингибитор Xa фактора ривароксабан -способны угнетать как системный, так и местный вос-палительные процессы, напрямую или опосредо-ванно активируя тромбин [21]. Влияние ППОАК на ате-росклеротический процесс как проявление хрони-ческого воспаления изучали Illkyu-O.…”
Section: Introductionunclassified